2020
DOI: 10.1080/08927014.2019.1708334
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surface copper content onStenotrophomonas maltophiliabiofilm control using chlorine and mechanical stress

Abstract: This work aimed to evaluate the action of materials with different copper content (0, 57, 96 and 100%) on biofilm formation and control by chlorination and mechanical stress. Stenotrophomonas maltophilia isolated from drinking water was used as a model microorganism and biofilms were developed in a rotating cylinder reactor using realism-based shear stress conditions. Biofilms were characterized phenotypically and exposed to three control strategies: 10 mg l À1 of free chlorine for 10 min, an increased shear s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 62 publications
(71 reference statements)
1
2
0
Order By: Relevance
“…Bench-scale studies examining copper's antimicrobial efficacy have found discrepancies between culture-based and molecular-based numbers of L. pneumophila [121,122] that are also suggestive of a copper-induced VBNC state. Similar discrepancies have been noted for P. aeruginosa, Stenotrophomonas maltophilia, and M. avium [104,109,127,132,133]. Evidence of copper-induced VBNC activity is particularly strong in the case of P. aeruginosa, where one study applied multiple non-culture-based measures of viability [127,132].…”
Section: Confounding Effects Of Vbnc Bacteriasupporting
confidence: 52%
See 1 more Smart Citation
“…Bench-scale studies examining copper's antimicrobial efficacy have found discrepancies between culture-based and molecular-based numbers of L. pneumophila [121,122] that are also suggestive of a copper-induced VBNC state. Similar discrepancies have been noted for P. aeruginosa, Stenotrophomonas maltophilia, and M. avium [104,109,127,132,133]. Evidence of copper-induced VBNC activity is particularly strong in the case of P. aeruginosa, where one study applied multiple non-culture-based measures of viability [127,132].…”
Section: Confounding Effects Of Vbnc Bacteriasupporting
confidence: 52%
“…Addition of copper ions to solution from pipes or via CSI, at the bench and building-scale, has also been shown to inhibit the growth or reduce the frequency of OPs such as Staphylococcus spp. [98,99], Stenotrophomonas maltophilia [91,92,104], Acinetobacter baumannii [58,91,92], NTM [108,109], and P. aeruginosa [91,92,98,99,127,130].…”
Section: Copper Pipe As An Antimicrobial Materials In Premise Plumbingmentioning
confidence: 99%
“…The mechanism by which copper materials act to kill fungi is not well understood [17]. The proposed mechanism of antifungal activity of synthesized CuONPs could be that CuONPs might have induced stress on C. albicans which led to the endogenous generation of reactive oxygen species (ROS) and subsequently caused damage to the cell membrane of C. albicans [18]. It might also be possible that the synthesized CuONPs inhibited ergosterol biosynthesis in C. albicans thus leading to the death of the fungi.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%